Higher Education and Myanmar’s Economic and Democratic Development - Kamibeppu, Takao; Chao, Jr., Roger Y. (International Higher Education, 2017)
This article argues that higher education plays a key role in Myanmar’s sustainable economic development and democratic transition. Establishing legal frameworks, supporting the implementation of institutional autonomy, incorporating citizenship education, and making full use of the country’s ASEAN membership are recommended.